Pengaruh Model Pembelajaran Berbasis Inkuiri Tentang Materi Perubahan Lingkungan terhadap Hasil Belajar Peserta Didik Kelas X di SMAN 1 Panyabungan Selatan - Siti Aminah (STKIP ROKANIA, 2023)
This study aims to determine the effect of inquiry-based learning models on student learning outcomes. The problems at SMAN 1 Panyabungan Selatan are that the learning activities are still teacher-centered, the varied learning models have not been implemented, and the students' learning outcomes are low. Efforts that can be made are to apply an inquiry-based learning model about environmental change material in biology learning.This research is a quasi-experimental research using Randomized Control Group Posttest Only Design. The research population was all students of class X MIA SMAN 1 Panyabungan Selatan for the academic year 2021/2022. The research sample was students of class X MIA 2 as the experimental class and class X MIA 1 as the control class. Sampling using total sampling technique. The instrument used in this study was a posttest question sheet in the form of multiple choice. Data analysis used hypothesis testing because the data were normally distributed and had homogeneous variations.Based on the results of the study, it is known that the learning outcomes of students in the experimental class are higher than the control class, with an average value of the experimental class (78.03) and the control class (72.85). Data analysis showed a significance value of 0.047 <0.05. So it can be concluded that the application of the inquiry learning model has a significant positive effect on student learning outcomes in class X biology learning at SMAN 1 Panyabungan Selatan.